Active study: undetected prevalence and clinical inertia in the treatment of breakthrough cancer pain (BTcP) - Camps Herrero, C.; Reina Zoilo, J. J.; Monge Martín, D.; Caballero Martínez, F.; Guillem Porta, V.; Aranda Aguilar, E.; Carrato Mena, A.; Díaz-Rubio García, E.; García-Foncillas López, J.; Feijóo Saus, M.; López López, R. (Clinical & translational oncology, 2019)
Aims To prove if there is clinical inertia in the identification and treatment of episodes of breakthrough cancer pain (BTcP), comparing actual results from clinical practice with clinical oncologists’ prior perception. Design Observational and descriptive study, using information collected by practising medical oncologists, at three moments: (a) questionnaire regarding their professional judgement of the handling of patients with BTcP in their practice, (b) cross-sectional clinical screening, to detect possible existing cases of BTcP in a representative sample of their patients, (c) retrospective self-audit of clinical case histories of patients diagnosed with BTcP to find out about how it has been handled. Participants and study period A random sample on a state level of 108 specialists in medical oncology. 540 patients who suffer some type of cancer pain on the designated study date for each specialist (July–December 2016). Results The global prevalence of BTcP in the study sample covered 91.3% of the patients who were suffering some type of cancer pain. Barely 2% of the doctors surveyed suspected figures around this mark. 40.9% of the cases had not been previously detected as BTcP by their doctors. Although 90% of the patients who had previously been diagnosed with BTcP received a specific analgesic treatment for the symptoms, 42% of those patients with known BTcP were not able to control their episodes of pain. Conclusions Clinical inertia is a serious problem in the handling of BTcP in medical oncology services, where it is the subject of a significantly low level of detection and treatment, despite the contrasting perception of specialists.